2015
DOI: 10.1007/s00464-015-4378-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-port versus conventional laparoscopic total extra-peritoneal inguinal hernia repair: a prospective, randomized, controlled clinical trial

Abstract: The outcomes after laparoscopic TEP inguinal hernia repair with a single-port device are similar but not superior to the conventional technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Compared to the Lai et al study, the Luo et al study had more data for its TEP analysis (from three additional studies) and its TAPP analysis (from one additional study) . However, Luo et al included data from both the interim and final reports by Wijerathne et al in their quantitative analysis . In the present review, we did not perform any quantitative analysis with data from the interim study.…”
Section: Current Evidencementioning
confidence: 89%
See 2 more Smart Citations
“…Compared to the Lai et al study, the Luo et al study had more data for its TEP analysis (from three additional studies) and its TAPP analysis (from one additional study) . However, Luo et al included data from both the interim and final reports by Wijerathne et al in their quantitative analysis . In the present review, we did not perform any quantitative analysis with data from the interim study.…”
Section: Current Evidencementioning
confidence: 89%
“…The 2014 study by Lai et al incorporated eight clinical trials—two on percutaneous extraperitoneal closure (PEC) , one on TAPP , and five on TEP —in its quantitative analysis; the eight trials had a total of 926 patients . A study by Luo et al published in 2017 included 17 clinical trials—2 on PEC , 2 on TAPP , and 13 on TEP —in its quantitative analysis; the 17 trials had a total of 1737 patients . The 2016 study by Sajid et al incorporated 15 trials—2 on PEC , 1 on TAPP , 11 on TEP , and 1 with combined results from TAPP and TEP —in its quantitative analysis; the 15 trials had a total of 1651 patients .…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A maximum of 2 stars can be given for comparability. Each study was classified as either low quality (0-5) or high quality (6)(7)(8)(9), and the lowquality studies were excluded.…”
Section: Quality Assessment Of the Studiesmentioning
confidence: 99%
“…For example, longer surgical procedures mean that patients are exposed to protracted anesthesia, which not only increases the direct cost of the procedure but also the morbidity and even mortality rates. Several studies have reported that the mean operative time was significantly shorter in the CLH group, 6,8 but others have revealed there was no significant difference between the CLH and SILH procedures. [9][10][11][12] Other concerns also arise, for example, SILH need a larger incision in abdominal wall than CLH, and this may potentially increase risk for port-related complications after single-port surgery, such as trocar site hernia.…”
Section: Introductionmentioning
confidence: 97%